## Trending News

# Use the Remainder Theorem. 11. (x^3 - 3x^2 + 4x +10)/ (x+1)?

will mark best answer :)

### 6 Answers

- MyRankLv 61 month agoFavorite Answer
x³-3x²+4x+10/(x+1)

f(x) = x³-3x²+4x+10

x+1 = 0 →x = -1

f(-1) = (-1)³-3(-1)²+4(-1)+10

= -1-3-4+10 ≠ 0

(x+1) ) x³-3x²+4x+10 (x²-4x+8

x³+x²

- -

____________

-4x²+4x

-4x²-4x

+ +

____________

8x+10

8x+8

- -

____________

2

Source(s): http://myrank.co.in/- Login to reply the answers

- ComoLv 71 month ago
x + 1 = x - (-1)

f (-1) = - 1 - 3 - 4 + 10 = 2____remainder

- Login to reply the answers

- Engr. RonaldLv 71 month ago
(x^3 - 3x^2 + 4x +10)/ (x+1)

f(-1) = (-1)^3 - 3(-1)^2 + 4(-1) + 10 = 2 answer//

- Login to reply the answers

- PhilipLv 61 month ago
Put f(x) = (x^3 -3x^2 +4x +10)

f(-1) = (-3-3-4+10) = 0. Therefore f(x) has (x+1)

as a factor of f(x) and, if we divide f(x) by (x+1),

the remainder will b 0.

- Login to reply the answers

- How do you think about the answers? You can sign in to vote the answer.
- KrishnamurthyLv 71 month ago
f(x) = (x^3 - 3x^2 + 4x + 10)

if x = -1, f(x) = -1 - 3 - 4 + 10 = 2

- Login to reply the answers

- PopeLv 71 month ago
Let f(x) = x³ - 3x² + 4x + 10.

When dividing f(x) by (x + 1), the remainder is f(-1). That gives you the remainder only. It does not tell you the quotient. Synthetic division would be the way to go about that.

- Login to reply the answers